Chapter The Hittite King as Administrator of the Land - Torri, Giulia (Studia Asiana, 2023)
In recent years archaeological investigation has made an important contribution for ascertaining the possible relationship between the center of the kingdom, namely the king and his capital city, and the regions at the core of the kingdom in different periods of Hittite history. The empire was not a monolithic entity but a complex web of interactions. In this frame the Hittite king emerges in his several roles. In this study I have chosen to focus on the king's administrative role and the way in which he was present in the territory through a controlled system of land allocation.